Deconstructing Black Swans: An Introductory Approach to Inherited Metabolic Disorders in the Neonate. (August 2015) - Ah Mew, Nicholas; Viall, Sarah; Kirmse, Brian; Chapman, Kimberly A.
Abstract : Background: Inherited metabolic disorders (IMDs) are individually rare but collectively common disorders that frequently require rapid or urgent therapy. Purpose: This article provides a generalized approach to IMDs, as well as some investigations and safe therapies that may be initiated pending the metabolic consult. Methods/Search Strategy: An overview of the research supporting management strategies is provided. In addition, the newborn metabolic screen is reviewed. Findings/Results: Caring for infants with IMDs can seem difficult because each of the types is rarely seen; however, collectively the management can be seen as similar. Implications for Practice: When an IMD is suspected, a metabolic specialist should be consulted for expert advice regarding appropriate laboratory investigations and management. Because rapid intervention of IMDs before the onset of symptoms may prevent future irreversible sequelae, each abnormal newborn screen must be addressed promptly. Implications for Research: Management can be difficult. Research in this area is limited and can be difficult without multisite coordination since sample sizes of any significance are difficult to achieve.